2014
DOI: 10.3892/etm.2014.1636
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of sodium houttuyfonate on synovial proliferation in vitro in cells from a patient with rheumatoid arthritis

Abstract: The aim of the present study was to investigate the inhibitory effect of sodium houttuyfonate (SH) on synovial cell proliferation in vitro. Primary cells were obtained from the synovial tissue of a patient with rheumatoid arthritis (RA). The cells were divided into five treatment groups as follows: the control group (group 1), 25 μg/ml SH-treated group (group 2), 50 μg/ml SH-treated group (group 3), 100 μg/ml SH-treated group (group 4) and the 200 μg/ml SH-treated group (group 5). Following seven days of treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Many studies showed the Tripterygium ingredients have the properties to promote FLS apoptosis and cell cycle arrest and inhibit FLS autophagy ( Xu, 2013 ; Xu et al., 2013 ; Lei et al., 2015 ; Su et al., 2017 ; Wong et al., 2019 ). It may be relevant to the increased expression of Bax/Bcl-2, Caspase-3, Caspase-9, and regulating by Ca2+/calmodulin-dependent protein kinases beta (CaMKK)-AMPK-mTOR signaling pathway.…”
Section: The Role Of Tripterygium Ingredients On Fls and The Moleculementioning
confidence: 99%
“…Many studies showed the Tripterygium ingredients have the properties to promote FLS apoptosis and cell cycle arrest and inhibit FLS autophagy ( Xu, 2013 ; Xu et al., 2013 ; Lei et al., 2015 ; Su et al., 2017 ; Wong et al., 2019 ). It may be relevant to the increased expression of Bax/Bcl-2, Caspase-3, Caspase-9, and regulating by Ca2+/calmodulin-dependent protein kinases beta (CaMKK)-AMPK-mTOR signaling pathway.…”
Section: The Role Of Tripterygium Ingredients On Fls and The Moleculementioning
confidence: 99%
“…joints and is known to have the following pathological characteristics: Auto-antibody production, synovial cell hyperplasia, inflammatory cell infiltration (such as neutrophile granulocytes and macrophages), pannus production and destruction of bones and cartilage, which finally lead to the destruction and lack of function of a whole joint (9). According to official statistics, rheumatoid arthritis is an important cause of productivity loss and extremity disability in China, with a morbidity rate of 0.32-0.36% (10).…”
mentioning
confidence: 99%
“…Primary cells of synovial tissue were collected from RA patients, cultured and subjected to SH treatment. Interestingly, post treatment, synovial proliferation in SH treatment groups were markedly lower than the control group (P < 0.05) in a dose dependent manner, with 200 μg/mL SH showing the highest inhibitory effects ( Li et al., 2014 ).…”
Section: Therapeutic Activities Of H Cordatamentioning
confidence: 93%